Potret Sikap dan Pemertahanan Bahasa Indonesia Anak-Anak Pekerja Migran di Sanggar Bimbingan Kampung Pandan Malaysia dalam Perspektif Pendidikan Berkelanjutan - Sahrul Romadhon; Iswah Adriana; Agus Purnomo Ahmad Putikadyanto; Albaburrahim Albaburrahim (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Language is a fundamental component of cultural identity; therefore, language attitude plays a crucial role in the sustainability of a language. From the perspective of sustainable education, the maintenance of the Indonesian language represents an important effort by non-formal educational institutions to provide educational access for migrant workers’ children while also contributing to the development of human resources with strong character and national identity. This study aims to describe language attitudes and the efforts to maintain the Indonesian language among migrant workers’ children at Sanggar Bimbingan Kampung Pandan, Malaysia. This research employs a qualitative approach using a descriptive method with a case study design. Data were collected through non-participant observation, recording, note-taking techniques, and interviews. The findings indicate that the majority of children exhibit positive attitudes toward the Indonesian language, as reflected in their sense of pride and loyalty in using it, despite living in a multilingual environment dominated by Malay. Language maintenance efforts are carried out through non-formal education at the learning center by teachers, family involvement, and peer interaction. However, instances of code-mixing were also identified, involving Indonesian, Malay as the children’s first language, and their respective regional languages. These findings highlight that sustainable education plays a significant role in preserving the linguistic and cultural identity of migrant workers’ children as part of sustainable development.